2016
DOI: 10.1016/j.chemphyslip.2016.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the role of sphingolipids in cystic fibrosis lung disease

Abstract: Cystic fibrosis (CF), one of the most common lethal hereditary diseases of white European populations, is caused by loss-of-function mutations in the CF Transmembrane conductance Regulator (CFTR) gene. One of the main causes of mortality is the onset of CF lung disease, which is characterized by chronic infection and inflammation resulting in the progressive remodelling, irreversible damage and fibrosis of the airways. An increasing number of studies indicate that sphingolipids are crucial players in pulmonary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 88 publications
1
31
0
Order By: Relevance
“…Sphingolipid dysregulation is a well-known occurrence following insult or injury of any kind to the lung. Elevated levels of ceramide or dysregulation of the ceramide/S1P axis are detected in many pathological conditions, including those observed following radiation insult 67 69 . The hydrolysis of sphingomyelin leading to the production of ceramide following injury or stress to the lung is a well characterized pathway; this sphingomyelin cycle is believed to be responsible for the decreases in the detection of these lipids observed here.…”
Section: Resultsmentioning
confidence: 99%
“…Sphingolipid dysregulation is a well-known occurrence following insult or injury of any kind to the lung. Elevated levels of ceramide or dysregulation of the ceramide/S1P axis are detected in many pathological conditions, including those observed following radiation insult 67 69 . The hydrolysis of sphingomyelin leading to the production of ceramide following injury or stress to the lung is a well characterized pathway; this sphingomyelin cycle is believed to be responsible for the decreases in the detection of these lipids observed here.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies in different CF models strongly support the existence of a relationship between SLs, inflammatory response, and susceptibility to bacterial infection. In particular, increased PM Cer levels in CF bronchi seem to be correlated with the proinflammatory status characterizing CF lung disease [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several factors contribute to the severity of CF inflammation. Among these, an increasing number of studies highlight that sphingolipids (SLs) play an important regulatory role in CF pulmonary infection and inflammation [ 6 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Here we found that BSS partly reduces the activation of the PKCα isoform in a completely different model, namely the bronchial epithelial cells challenged with P. aeruginosa ( Figure 7 ), which we found involved with a relevant pro-inflammatory role in the Ca 2+ -dependent signaling machinery, leading to IL-8 gene expression induced by P. aeruginosa in CF bronchial epithelial cells (Bezzerri et al, 2011b). The role of BSS in the organization of lipid rafts of plasma membranes and in the modulation of ceramide (Beck et al, 2007; Hąc-Wydro, 2013; Grosjean et al, 2015) also opens interesting insights in relation to sphingolipid metabolism and inflammation in CF lung disease (for review see Aureli et al, 2016). …”
Section: Discussionmentioning
confidence: 99%